MRI Markers of Small Vessel Disease and the APOE Allele in Cognitive Impairment - Shams, Mana; Shams, Sara; Martola, Juha; Cavallin, Lena; Granberg, Tobias; Kaijser, Magnus; Wintermark, Max; Westman, Eric; Aspelin, Peter; Kristoffersen Wiberg, Maria; Wahlund, Lars-Olof (Frontiers in Aging Neuroscience, 2022)
OBJECTIVE The apolipoprotein E (APOE) ε4 allele is the main genetic risk factor for dementia and Alzheimer’s disease (AD), but the underlying mechanism for the increased risk is not well understood. Cerebral small vessel disease (SVD) is prevalent among patients with cognitive impairment and is thought to play an important role in the pathophysiology of dementia. We aimed to investigate the association between the APOE ε genotype and magnetic resonance imaging (MRI) markers of SVD in a memory clinic population. MATERIAL AND METHODS This is a cross-sectional study with a total of 520 patients undergoing dementia investigation, including an MRI brain scan and APOE genotyping in all patients enrolled, and cerebrospinal fluid (CSF) analysis for routine AD biomarkers in 399 patients. MR images were assessed for markers of SVD: cerebral microbleeds, cortical superficial siderosis, intracerebral haemorrhage, white matter hyperintensities, lacunar infarcts and enlarged perivascular spaces. RESULTS APOE ε4 carriers with AD had a higher number of cerebral microbleeds when looking at all brain regions and lobar brain regions (P<0.001). A lower number of cerebral microbleeds were seen in APOE ε2 (P<0.05), ε3 and ε3/3 carriers (P<0.001) when looking at all brain regions. A higher number of cerebral microbleeds in deep and infratentorial regions were seen in APOE ε2 and ε3 (P<0.05). In APOE ε4/4 carriers, cerebral microbleeds, cortical superficial siderosis, white matter hyperintensities and enlarged perivascular spaces were associated with lower levels of CSF amyloid β (Aβ) 42 in the whole cohort, and in individuals with AD and mild cognitive impairment (P<0.05). CONCLUSION APOE ε4 is associated with MRI markers of SVD related to amyloid pathology, specifically cerebral microbleeds and Aβ42 plaque formation in the brain, as reflected by decreased CSF Aβ42 levels, whereas APOE ε3 and ε2 are associated with markers of hypertensive arteriopathy, as reflected by the association with cerebral microbleeds in deep and infratentorial brain regions.